(untitled) (Journal of Environmental Bioremediation and Toxicology, 2020)
A predictive mathematical modeling of the biofilm potentials of phytochemicals from A. philippense extract and adhesion with P. aeruginosa was studied for the very first time. Eight different kinetic models Von Bertalanffy, Baranyi-Roberts, modified Schnute, modified Richards, modified Gompertz, Modified Logistics and latest Huang were used to get values for the kinetic constants. Von Bertalanffy of the entire model was found to be the best model with the highest adjusted R2 value with the lowest RMSE value. The accuracy and bias factors values were close to one (1.0). The parameters obtained from von Bertalanffy model for P. aeruginosa and chloramphenicol were K 1.551 ( 95% C.I 1.385 to 1.718) and 1.617 (95% C.I 1.204 to 2.031), A -1.055( 95% C.I -1.492 to -0.61) and -1.142 (95% C.I -1.612 to -0.67), Um 1.041 (95% C.I 0.740 to 1.342) and 0.744 (95% C.I 0.399 to 1.089) respectively. This finding shows the influence of von Bertalanffy model in the roles of phytochemicals from Adantum philippense in the biofilm potentials and adhesion with P. aeruginosa against foodborne pathogens.